Scaling behavior of dynamic ferroelectric hysteresis in soft PZT ceramic: Stress dependence - Rattikorn Yimnirun (2018)
Effects of electric field-frequency, electric field-amplitude, and mechanical stress on the hysteresis area were investigated on soft PZT ceramic. At stress-free condition, the investigation found the area scales with frequency and field-amplitude in power-law form, 〈A〉 α f-0.25E0; however, with different set of exponents in comparing to those in the investigation on thin films structure. On the other hand, with compressive stresses turning on, the same set of the exponents with the stress-free condition is found to confirm universality. In addition, the scaling form of the area to triple parameters; i.e., frequency, field-amplitude, and stress in a power law form, 〈A〉 - 〈Aρ=0= 〈 A Aρ= 0〉 α f0.25- 0.25 E0ρ0.44, was obtained.